MON-289 Pituitary Metastasis: A Systematic Review - Parekh, Shrina (J Endocr Soc, 2020)
Metastatic lesions to the pituitary are uncommon as well as concerning as they do not always have a characteristic radiographic appearance and can be easily missed. We conducted a systematic review of all the published cases and case series of pituitary metastasis to further understand the unique characteristics of these lesions. Using Pubmed and Embase as the primary search engines, we reviewed all cases published from January 1980 to July 2019. A total of 175 unique cases were included in the study. Over 400 cases were collected amongst which a total of 278 cases were included in the study. As part of a challenge with any retrospective study some data points were missing from cases reviewed. Only English language publications were included in the study. The study revealed a predominance of females with 121 cases. Median age was noted to be 61 years. Only 40 patients had previously known metastatic disease. 70 patients were noted have primary cancer arising in the breast which was noted to be the most common primary cancer followed by 64 cases of primary cancer arising from the lungs. Majority of the patients (162 cases) had pituitary hypofunction with deficiency of one or more pituitary hormones. 97 cases were reported to have diabetes insipidus on presentation. Only 40 patients had no visual field deficits whereas 77 patients were reported to have abnormal eye movements. Displacement of the gland superiorly towards optic chiasm was the most common radiographic features in 137 reported cases. Although not commonly reported in most of the published literature, 45 cases were noted to have bony erosion due to expansion of the gland. Only 5 cases were reported to have no contrast enhancement, although many case reports did not specify contrast enhancement of the pituitary. 22 cases were noted to have an aggressive or rapid growth pattern of the pituitary. 13 cases were noted to have edema around the optic chiasm. The pituitary should not be overlooked as a site of metastasis. Many cases can present asymptomatically without biochemical or radiographic characteristics of metastatic lesion. Any biochemical or clinical sign of pituitary pathology in a patient with known cancer should raise suspicion for sellar metastasis. Unique radiographic characteristics should alert the clinicians to consider this possibility. Our study revealed many unique characteristics of metastatic lesions of the pituitary. This should allow clinicians to become aware of the more common findings in these patients allowing prompt diagnosis.